2016
DOI: 10.3390/ijerph13121237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attitudinal, Situational and Demographic Factors on Annoyance Due to Environmental Vibration and Noise from Construction of a Light Rapid Transit System

Abstract: The aim of this paper is to determine what non-exposure factors influence the relationship between vibration and noise exposure from the construction of a Light Rapid Transit (LRT) system and the annoyance of nearby residents. Noise and vibration from construction sites are known to annoy residents, with annoyance increasing as a function of the magnitude of the vibration and noise. There is not a strong correlation between exposure and levels of annoyance suggesting that factors not directly related to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A small number of studies have examined factors that may affect annoyance from vibrations. Wong-McSweeney et al found that concern of property damage and sensitivity to vibrations from construction of a transport system were two important modifying factors, as were age, ownership, and visibility of the construction work [ 29 , 34 ]. Visibility of the source of the stimulus has also been reported to reduce annoyance in Sweden [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of studies have examined factors that may affect annoyance from vibrations. Wong-McSweeney et al found that concern of property damage and sensitivity to vibrations from construction of a transport system were two important modifying factors, as were age, ownership, and visibility of the construction work [ 29 , 34 ]. Visibility of the source of the stimulus has also been reported to reduce annoyance in Sweden [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the direction of association is difficult to elucidate, as worry and annoyance are interlinked, worry is an important modifying factor. Previous studies have shown that concern for property damage has been an important moderator of annoyance [ 34 ], despite vibration exposure below levels shown to result in actual physical damage to the property [ 35 ]. This raises the possibility that it is not only the vibrations themselves that are annoying but it may also be that the resultant worry is an indirect source of annoyance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have used lichens for documenting metal deposition across the world as it is well known that lichen absorbs metals and nitrogen [2,16,[34][35][36]. Researchers have evaluated the distribution of contaminants in relation to wind patterns in large population centers like Los Angeles as well as industrial areas [3,37].…”
Section: Discussionmentioning
confidence: 99%
“…Polluted air can typically contain NO x , SO x , CO 2 , aerosols, particulate matter (PM 10 , PM 2.5 ), heavy ("trace") metals, and organic pollutants from sources of fossil fuel activities [2,3]. Some metals (e.g., Pb, Cd, Cr) are known to be hazardous because of bioaccumulation and long retention times in tissues of living organisms, including humans [2]. These pollutants are not only suspended in air as particulates, but are found in tissues of plant and animal species within a given area, resulting from deposition onto and uptake processes.…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas affected by noise typically include schools, residence, office buildings, markets, airports, and subway stations [29][30][31][32][33]. To predict the structure-radiated noise, methods such as numerical methods, empirical formulas, or experimental methods can be adopted [34,35]. The empirical formula method is widely used because of its convenience and low cost [36].…”
Section: Introductionmentioning
confidence: 99%